Knowledge, Attitude, Practice of Adverse Drug Reaction Reporting Among Healthcare Professionals in A Tertiary Care Hospital - Neelam Injeti,; K. Padmini,; P Swetha,; B Vyshnavi,; K Harshith, (International Journal of Pharma and Bio Sciences, 2022)
According to the World Health Organization, Adverse Drug Reaction is defined as ‘any response to a drug which is noxious and unintended, and which occurs at doses normally used in human for prophylaxis, diagnosis, or treatment of sickness, or for the changes of physiological capacity’. Monitoring of ADR is carried out by different methods of which, spontaneous reporting is commonly practiced. However, lack of knowledge and awareness are the barriers of under-reporting. Health care professionals are expected to consider ADR reporting as their professional obligation, since ADR reporting is important to improve patient care, safety and overall health. The success or failure of a spontaneous reporting system depends on the active participation of health care professionals. Knowledge, Attitude, Practice study (KAP) measures the Knowledge, Attitude and Practice of a community. It serves as an educational diagnosis of the community. The main purpose of this KAP study is to explore the changes in Knowledge, Attitude and Practices of the community. A prospective cross-sectional study was conducted for a 6-month's duration in a tertiary care hospital. Data of total 175 Healthcare professionals was collected, interpreted by Chi-square test and was analyzed in our study. Knowledge, Attitude, Practice were analyzed based on the responses given in the questionnaire form of survey. P-value is defined as the probability of the null-hypothesis being true. If the p-value is less than level of significance (0.05), it indicates that, a significant difference exists, i.e. Null hypothesis is rejected and the Alternative hypothesis is accepted, if the p-value is greater than the level of significance (0.05), it indicates that there is no significant difference of KAP among health care professionals. This study assesses the Knowledge, Attitude, Practice of ADR’s reporting among Healthcare professionals and also explains the major factor responsible for under-reporting.